Managing spontaneous community volunteers in disasters : a field manual - Orloff, Lisa. (Boca Raton, FL : CRC Press, 2011)
"History has demonstrated that it's not only possible, but extremely cost-effective, to organize and empower community volunteers to serve their own neighborhoods during times of crisis. Laying out the rationale and process by which emergency managers, community leaders, and non-governmental aid organizations can effectively harness volunteer resources, Managing Spontaneous Community Volunteers in Disasters: A Field Manual explains how to engage, train, and utilize spontaneous unaffiliated community volunteers (SUCV). The book details guidelines to help cultivate the required culture of collaboration and respect between community volunteers and emergency managers. It examines potential agency and community relevant roles for volunteers, and the need for flexible management solutions that incorporate spot screening and "just in time" training. Complete with templates that can be modified to suit the needs of any community; this accessible manual provides the tools to: Assess your agency's needs and challengesDevelop internal and external protocols to manage SUCs Establish effective spot screening and selection methods Engage community members in information-sharing and outreach campaigns Provides National Incident Management System (NIMS) compliant answers to address common barriers to using SUCVsDesigned to prepare leaders to handle any scale of emergency, the book supplies the skill-set needed to enable volunteers to respond to hazards safely and effectively. Integrating Orloff's on-the-ground experience with community organizing, a decade of research data on disaster management protocols, and recent psychosocial research, the book makes a strong case as to why community involvement in disaster response has such a positive impact on a community's resilient recovery.Praise for:Lisa Orloff has done an excellent job in both identifying a significant opportunity in emergency response and meticulously outlining how that opportunity can best be leveraged. The author should be commended for articulating this opportunity and packaging it in a manner that benefits the entire emergency response effort. Dr. Michael Chumer, New Jersey Institute of Technology"--Provided by publisher.
"The difference between citizen volunteers and official responders lies in the combination of training, experience, connection to official resources, and the authority to conduct operations, not in the willingness to help. Acknowledging that success in disaster response is based on the knowledge and resources that are immediately available, take into consideration that citizens also have a cultural understanding of the affected community that outside official responders will not. Community members also have the ability to connect to local resources that are immediately available, both material and human. The gap between those who hold important local and cultural knowledge, coupled with a willingness to help, and those with professional disaster management training and resources must be bridged to improve response and to address the mistakes that we have seen cost lives and property in the not-so-distant past. Taking these issues into account, the intent of this manual is twofold: (a) to give emergency managers and community leaders the tools to safely and effectively manage spontaneous community volunteers and (b) to provide guidance to managers and community leaders on ways to empower citizens to take a proactive role in their community's preparedness and response efforts"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Emergency management; Voluntarism